KAJIAN PSIKOLOGI TENTANG ISTIQAMAH PERSPEKTIF MAHASISWA - Husna, Hafizhah Al (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Abstract This study aims to analyze and prepare a conceptual framework that can be used as a research basis in Islamic Psychology. This research using a descriptive qualitative approach. The participants in this study were 57 students who were pursuing bachelor's and master's degrees, both on the island of Java and Sumatra. Research data was collected using the open-ended question method which contains one open question, namely